2017
DOI: 10.1016/j.jmgm.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of efficient docking strategies and structure-activity relationship study of the c-Met type II inhibitors

Abstract: Graphical AbstractTOC c-Met is a tyrosine kinase and an important therapeutic target for anticancer drugs. In present study, we systematically investigated the influence of a range of parameters on the correlation between experimental and calculated binding energies of type II c-Met inhibitors. Results from this study will form the basis for establishing an efficient computational docking approach for c-Met type II inhibitors design. Highlights• Testing a set of influences to the ranking ability of the docking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…[1][2][3][4] Type II inhibitors, such as cabozantinib, bind to an inactive conformation of MET, inhibiting a broader array of kinase targets. 5 A limited number of studies have reported MET inhibitor-associated resistance. In this study, we have described a patient with EGFR-mutant lung adenocarcinoma clinically benefitting from combinatorial therapy of osimertinib and cabozantinib after simultaneous development of four MET mutations upon crizotinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Type II inhibitors, such as cabozantinib, bind to an inactive conformation of MET, inhibiting a broader array of kinase targets. 5 A limited number of studies have reported MET inhibitor-associated resistance. In this study, we have described a patient with EGFR-mutant lung adenocarcinoma clinically benefitting from combinatorial therapy of osimertinib and cabozantinib after simultaneous development of four MET mutations upon crizotinib treatment.…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that it should be taken into account for designing drugs with improved efficiency and selectivity profiles [25,26]. To be efficient, the molecular docking engines embedded within the virtual screening approaches must be adapted to handle such flexibility [27,28]. In the present work, we used the ensemble-docking strategy-previously recognized for its efficiency in drug design [29]-and show the benefit of an investigation using a large ensemble-docking on MET.…”
Section: Introductionmentioning
confidence: 98%
“…c-Met inhibitors are classified as type I and type II inhibitors according to the binding mode of inhibitors with c-Met. Usually, c-Met inhibitors of type I are single-target inhibitors that bind to the hinge region of the ATP pocket, and c-Met inhibitors of type II are multitarget inhibitors that bind to the hinge region and an extra hydrophobic pocket [8,9]. With the development of biology and pharmacology, the intracellular mechanisms have been elucidated, and research in small molecule inhibitors has made significant progress.…”
Section: Introductionmentioning
confidence: 99%